Penerapan Model Pembelajaran Menggunakan Pendekatan Saintifik di Sekolah Dasar - Ina Magdalena; Dewi Rachma Lestari; Aniq Insyirah; Siti Khoiriah (ISLAMIKA, 2020)
The study aims to describe the application of scientific learning models conducted at SDN Palsari 3. Thus study uses a qualitative approach with descriptive research type. The subjects in this study were teachers and students in elementary schools. Data collection techniques using observation, intervierws, and data analysis. Data analysisechniques used are the miles and huberman modelswich include data collection,data reduction, and data presentation. The validity test of the data used is the reliability test whichh is done by triangulation of sources. The results of the study indicate that the teacher has implemented a scientific approach to the maximum starting from the planning, implementation, and assesment in the learning process. The steps of the activities in the application of scientific learning which includes observing, asking, trying, reasoning and communicating activities that have been implemented by the teacher. Student activities in the learning process show that students have been to be active, enthusiastic and motivated.